Development of Chaplaincy in Independent Ukraine: Current State and Trends of Development - Ishchuk, Nataliia (Occasional papers on religion in Eastern Europe, 2020)
The preconditions and difficulties of the formation of the chaplaincy movement in contemporary Ukraine are systematized in this paper. It is shown that for a significant period of time after the proclamation of Ukraine’s independence, chaplaincy developed mainly by private initiatives of individual clergy or public organizations. In the first years of Ukraine’s independence, the main obstacles to its development were the atheistic legacy of the Soviet Union, ideological clichés, and the lack of a legal framework for the implementation of pastoral work. Nevertheless, as early as the 1990s, the chaplaincy ministry began to receive legal justification, significant international support, and public authority. This contributed to the development of both military and non-military chaplaincy. Currently, the most dynamic military chaplaincy yet is developing in the country, which operates not only in the Armed Forces of Ukraine, but also in the National Guard of Ukraine and the State Border Guard Service of Ukraine. The main activities of military chaplains in these structures are care for the religious needs of servicemen, individual pastoral care of personnel, religious and educational work, pastoral care of families of servicemen and veterans, social and charitable activities, etc. The beginning of hostilities against Ukraine in 2014 accelerated the pace of development of chaplaincy in these structures accompanied by the transition of chaplaincy from a volunteer to a professional basis. Non-military chaplaincy has also been developing rapidly, though with less formal regulation. The most common forms of non-military chaplaincy in Ukraine are health care chaplaincy, prison chaplaincy, student (youth) chaplaincy, orphan chaplaincy, etc. A common feature of military and non-military chaplaincy is the fact that cooperation of the state structures with the church institutions comes mainly within the framework of the religious institutions that are members of the All-Ukrainian Council of Churches and Religious Organizations. Prospectively, the authority of chaplaincy in Ukrainian society will strengthen, the legal principles of activity of chaplains will be established, and the number of chaplains and the quality of their training will increase.